2008
DOI: 10.1016/j.nbd.2008.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal choline supplementation attenuates neuropathological response to status epilepticus in the adult rat hippocampus

Abstract: Prenatal choline supplementation (SUP) protects adult rats against spatial memory deficits observed after excitotoxin-induced status epilepticus (SE). To examine the mechanism underlying this neuroprotection, we determined the effects of SUP on a variety of hippocampal markers known to change in response to SE and thought to underlie ensuing cognitive deficits. Adult offspring from rat dams that received either a Control or SUP diet on embryonic days 12-17 were administered saline or kainic acid (i.p.) to indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
79
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(94 citation statements)
references
References 115 publications
(198 reference statements)
14
79
1
Order By: Relevance
“…MCS also ameliorates dysfunction in rodent models of human disorders including fetal alcohol syndrome, Rett syndrome, epilepsy, and schizophrenia [58,60,62,63,108]. Since nerve growth factor (NGF) is involved in the maintenance of BFCNs during development and in DS models of axonal transport whereby NGF is inhibited, it is important to consider interaction(s) between neurotrophic activity and choline supplementation as well as hippocampal neuroplasticity and behavioral responses in Ts65Dn and 2N mice [26,31].…”
Section: Discussionmentioning
confidence: 99%
“…MCS also ameliorates dysfunction in rodent models of human disorders including fetal alcohol syndrome, Rett syndrome, epilepsy, and schizophrenia [58,60,62,63,108]. Since nerve growth factor (NGF) is involved in the maintenance of BFCNs during development and in DS models of axonal transport whereby NGF is inhibited, it is important to consider interaction(s) between neurotrophic activity and choline supplementation as well as hippocampal neuroplasticity and behavioral responses in Ts65Dn and 2N mice [26,31].…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal nutrition sets the stage for brain function in later life, in part, through the process of "metabolic imprinting," which controls the rate of neurotransmitter synthesis, storage, release, and uptake (e.g., Blusztajn et al 1998;Meck and Williams 2003;Wong-Goodrich et al 2008b). Numerous research reports have described the importance of choline for the developing fetus and neonate (e.g., Zeisel 2000Zeisel , 2004Zeisel , 2005Zeisel , 2006McCann et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, certain aspects of cholinergic metabolism in brain (specifically, acetylcholinesterase and high-affinity choline uptake) and behavior have been shown to be enhanced in DEF rats (e.g., Blusztajn et al 1998;Cermak et al 1998;Williams 1999, 2003;Wong-Goodrich et al 2008b). Additionally, although hippocampal slices from DEF rats show increased thresholds for the induction of LTP (Pyapali et al 1998;Jones III et al 1999), it is not a trivial point that all slices showed LTP, i.e., DEF rats still have an active hippocampus, albeit with altered function.…”
Section: Discussionmentioning
confidence: 99%
“…) of choline in diet) supplementation from day 12 to 17 of pregnancy [107,108,111,[121][122][123] Improved age-related memory in choline supplemented group www.global-challenges.com [109] Offsprings of choline supplemented group had increased levels of hippocampal BDNF, NGF, and IGF-1. Choline supplementation also caused less seizure-induced hippocampal neurodegeneration, dentate cell proliferation, hippocampal GFAP mRNA expression levels, prevented the loss of hippocampal GAD65 protein and mRNA expression, and altered growth factor expression patterns Rat Third trimester ethanol (5.25-6 g kg…”
Section: Hypomethylation Of the Pancreatic Il13ra2 Genementioning
confidence: 99%